Investigation on Ethnomedicinal values of Zingiber OfficinaleRoscoe. - A Remedial Plant - Fatima, Ayesha; Alam, Mahwish (International Journal of Psychosocial Rehabilitation, 2020)
All the plants growing on this earth have their specific values. The traditional or herbal utilization of ethnomedicinal importance of Zingiber OfficinaleRoscoe are very beneficial for human being. Zingiber OfficinaleRoscoe belongs to Zingiberacae family. It’s a perennial creeping in plant having thick tuberous rhizome, long leaves, and yellow green flowers. This can be classified as a type of storage root which is having pungent taste. It is one of the famous species across the world. From traditional treatment and prevention of a number of diseases and conditions that reduce inflammation and pain in joints, migraine, antiseptic, bactericidal, headaches, carminative, nausea, analgesic, antispasmodic, tonic, anti-emetic, stimulant, cephalic, stomachic, expectorant, febrifuge, laxative, rubefacient, and sudorific. The ginger’s medicinal properties and its knowledge deliver a very good platform for investigators and researchers for future aspect of Zingiber Officinale Roscoe.